Unraveling the Sex Chromosome Heteromorphism of the Paradoxical Frog Pseudis tocantins - Gatto, Kaleb Pretto (PLoS One, 2016)
The paradoxical frog Pseudis tocantins is the only species in the Hylidae family with known heteromorphic Z and W sex chromosomes. The Z chromosome is metacentric and presents an interstitial nucleolar organizer region (NOR) on the long arm that is adjacent to a pericentromeric heterochromatic band. In contrast, the submetacentric W chromosome carries a pericentromeric NOR on the long arm, which is adjacent to a clearly evident heterochromatic band that is larger than the band found on the Z chromosome and justify the size difference observed between these chromosomes. Here, we provide evidence that the non-centromeric heterochromatic bands in Zq and Wq differ not only in size and location but also in composition, based on comparative genomic hybridization (CGH) and an analysis of the anuran PcP190 satellite DNA. The finding of PcP190 sequences in P. tocantins extends the presence of this satellite DNA, which was previously detected among Leptodactylidae and Hylodidae, suggesting that this family of repetitive DNA is even older than it was formerly considered. Seven groups of PcP190 sequences were recognized in the genome of P. tocantins. PcP190 probes mapped to the heterochromatic band in Wq, and a Southern blot analysis indicated the accumulation of PcP190 in the female genome of P. tocantins, which suggests the involvement of this satellite DNA in the evolution of the sex chromosomes of this species.